Examining the Factor Structure of the Organizational Commitment Questionnaire in the Vietnamese Educational Context (Journal of Contemporary Educational Policies and Practices, 2024)
In contemporary organizational research, organizational commitment has emerged as a crucial concept in comprehending employees' behavior within the workplace, reflecting their identification with an organization and dedication to its objectives. Despite its significance, the existing literature reveals a scarcity of research on this subject within the Vietnamese educational context. Therefore, the primary objective of the current study was to validate the factor structure of the 24-item Organizational Commitment Questionnaire (OCQ) in Vietnam. Both exploratory and confirmatory factor analyses were employed to analyze the data obtained from 706 high school teachers. The results obtained from the factorial analyses strongly support the validity of the three-factor model of the original OCQ, which comprises affective commitment, continuance commitment, and normative commitment. The results include statistical measures such as factor loadings, eigenvalues, and variance explained, indicating how well the observed data align with the proposed three-factor model. This validation is crucial for understanding and measuring organizational commitment within the Vietnamese settings. Educational researchers can rely on these findings to better assess teachers’ commitment within schools. This study suggests further examining the reliability and validity of the OCQ with a wide range of participants among teachers at both elementary and secondary school levels.
Keywords: Affective commitment; continuance commitment; factorial analysis; normative commitment; organizational commitment; Vietnamese teachers